“People want better”: a qualitative exploration of stakeholders’ views on introducing well-being coordinators in the screen industry - John Goodwin; Eleanor McSherry; Ryan Goulding; James O’Mahony; Rachael O’Callaghan; Ciara Chambers (International Journal of Qualitative Studies on Health & Well-Being)
Purpose There are several factors that negatively impact the well-being of those working in the screen industry. Consequently, the need to introduce Well-being Coordinators has been identified. This study explored the experiences of participants who undertook a Well-being Coordination course tailored for the screen sector. Additionally, it sought to delve into perspectives regarding well-being within the screen industry. Methods Semi-structured interviews were conducted. The study was guided by an interpretive descriptive approach. Reflexive thematic analysis was used to analyse data. Findings Five themes were identified: Opportunities and challenges working in the screen industry, co-existing with harassment, the need for change: importance of wellbeing, becoming a well-being co-ordinator: learning from the course, and the future of the well-being co-ordinator role: opportunities and challenges. The reality that cast and crew co-exist with several forms of harassment within the industry was noted. Despite this, there is hope for the future of the screen sector, particularly the positive impact the role of the Well-being Coordinator could have. Conclusions The experiences of professionals across the screen industry vary; however, a pervasive culture of bullying and harassment is commonplace. Through the introduction of Well-being Coordinators, there is the potential to enact positive change.